Grenzen im Transit: Zur Konstitution politischer Subjektivitäten in transmigrantischen Räumen - Kron, Stefanie (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2010)
This essay deals with the chances and problems of intersectionality and border feminism for empirical research on transnational migration. Empirically based on a qualitative research of the return movement of guatemalan refugees, the focus of the paper will be on the importance of borders and experiences of bordercrossings for the formation of political subjectivities within transmigrant communities. Parting from a postcolonial perspective the theoretical and methodical inputs and limits of the concepts of intersectionality and border feminism will be discussed. Secondly, the developed analytical framework will be applied to the return movement of guatemalan war refugees.